Lower incisor changes on basal bone and in relation to the lower face: combined growth and treatment effects in the late mixed-dentition - Woods Michael (Sciendo, 2002)
This study was designed to determine and compare the ranges of combined growth and late mixed-dentition treatment changes in the positions of the lower incisors, either on basal bone or in relation to the APog line. While there was considerable individual variation, movements of the lower incisors in relation to APog were found to be related more to changes in the angulation of the APog line itself, than to the movements of the incisors on the basal bone. In individual cases in which considerable forward movement had occurred at pogonion and in which deep anterior over-bites had been reduced, it was often found that the lower incisors had moved forward considerably in relation to the APog line without necessarily having moved forward at all on the underlying basal bone. It was concluded therefore that, in such cases, lower incisor movements on basal bone may actually occur in the opposite direction to those in relation to the APog line because of the complex interaction of changes occurring in the vertical and horizontal positions of both point A and pogonion. In these cases, it seems possible for the lower dentoalveolus to be passively carried forward with growth of the underlying basal bone, once any deep overbite has been reduced.